Evaluation of a school of medical students' attitudes towards violence against women in Istanbul - DAVUN, SELİN; KURNAZ AY, MERVE; KARAVUŞ, MELDA; HIDIROĞLU, SEYHAN (My University, 2022)
Introduction: Violence against women has become an important public health and human rights issue. In this study, we aimed to determine and evaluate the attitudes of students in a medical school in Istanbul towards violence against women. Material and Methods: This is a descriptive study. The population of the study consists of 1523 undergraduate students studying at the Faculty of Medicine of a university on the Anatolian side of Istanbul in the 2020-2021 academic year. The sample size was calculated as a minimum of 307 people with a 95% confidence interval and 5% margin of error and %50 prevalance (since the prevalence of medical students' attitudes towards violence against women is not known exactly, it was taken as 50%). This study was carried out with 504 participants in total. The research data were collected using a questionnaire designed to determine the sociodemographic characteristics of the participants and the "Attitudes towards Violence Scale (SITO)", which evaluates the attitudes of the participants towards violence. Results: Among the participants %65.3 were female and 34.7% were male. While 41.9% of the participants in this study were preclinical medical students, 58.1% were clinical medical students. There is a statistical significant difference between the total scores of men and women from the SITO (Attitudes towards Violence Scale) scale (p<0.001). While the mean SITO(Attitudes towards Violence Scale) total score of preclinical medical students was 32.38±0.37, the mean SITO(Attitudes towards Violence Scale) total score of clinical medical students was 33±0.47. Considering the scores obtained from the all SITO(Attitudes towards Violence Scale) subscales, there was a significant difference between whether the students were preclinical or clinical and the scores they got from the SITO(Attitudes towards Violence Scale) emotional subscale (p<0.05). When the scale scores of the participants were examined according to the region they were born, a significant difference was observed between the participants in terms of the scores obtained from the SITO (Attitudes towards Violence Scale) economic subscale according to the region of birth (p<0.05). Conclusion: Sex, class level, place of residence, region of birth, economic status of the students and their parents' work and education levels affect their attitudes towards violence against women
Keywords: Tıp; Sağlık Bilimleri; Medicine; Health Sciences; Klinik Tıp (MED); Klinik Tıp; Clinical Medicine (MED); CLINICAL MEDICINE; Medical students; violence; attitudes